The market chain analysis of live cattle in South Omo Zone, Southern Ethiopia - Kusse, Kutoya; Alemayehu, Yidnekachew; Ermias, Gedion; Darcho, Dawit (International Journal of Agricultural Research, Innovation and Technology, 2022)
This study focus on market chain actors and their functions they play in the market, to analyze the S-C-P of live cattle in the study area. Few traders dominated the market structure of live cattle in the study area. Degree of competition between traders varies and the live cattle market structure varies from loose oligopoly to tight oligopoly. This shows that in the study area few traders dominated market shares and earns abnormal profit. Entry barriers of the market are high market distant, characterize the market of live cattle and high transportation cost. In addition, market the structure varies for each cattle type. Int. J. Agril. Res. Innov. Tech. 12(1): 56-66, June 2022